Antibiotic Resistance Profiles of Haemophilus influenzae Isolates from Children in 2016: A Multicenter Study in China - Hong-Jiao Wang; Chuan-Qing Wang; Chun-Zhen Hua; Hui Yu; Ting Zhang; Hong Zhang; Shi-Fu Wang; Ai-Wei Lin; Qing Cao; Wei-Chun Huang; Hui-Ling Deng; Shan-Cheng Cao; et al. (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background and Objective. Haemophilus influenzae (HI) is a common cause of community-acquired pneumonia in children. In many countries, HI strains are increasingly resistant to ampicillin and other commonly prescribed antibiotics, posing a challenge for effective clinical treatment. This study was undertaken to determine the antibiotic resistance profiles of HI isolates from Chinese children and to provide guidelines for clinical treatment. Methods. Our Infectious Disease Surveillance of Pediatrics (ISPED) collaboration group includes six children’s hospitals in different regions of China. The same protocols and guidelines were used by all collaborators for the culture and identification of HI. The Kirby–Bauer method was used to test antibiotic susceptibility, and a cefinase disc was used to detect β-lactamase activity. Results. We isolated 2073 HI strains in 2016: 83.9% from the respiratory tract, 11.1% from vaginal secretions, and 0.5% from blood. Patients with respiratory isolates were significantly younger than nonrespiratory patients (P<0.001). Of all 2073 strains, 50.3% were positive for β-lactamase and 58.1% were resistant to ampicillin; 9.3% were β-lactamase-negative and ampicillin-resistant. The resistance rates of the HI isolates to trimethoprim-sulfamethoxazole, azithromycin, cefuroxime, ampicillin-sulbactam, cefotaxime, and meropenem were 71.1%, 32.0%, 31.2%, 17.6%, 5.9%, and 0.2%, respectively. Conclusions. More than half of the HI strains isolated from Chinese children were resistant to ampicillin, primarily due to the production of β-lactamase. Cefotaxime and other third-generation cephalosporins could be the first choice for the treatment of ampicillin-resistant HI infections.